Novel Isolates of Lactobacilli from Crop of Algerian Poultry as Potential Probiotic for Food Industry - Idoui, Tayeb; Sifour, Mohamed (International Journal of Biotechnology for Wellness Industries, 2023)
This study was aimed at selecting novel strains of Lactobacillus from crop of Algerian poultry. One hundred forty (140) lactobacilli strains were isolated and examined for their potentiality probiotic properties. From these isolated strains, nine appear to possess a probiotic value and highlighted a noticeable heterogeneity. The isolate L. plantarum G1 showed the best inhibitory activity against several indicator strains. Furthermore, the results showed that culture and neutralized supernatants exhibited varying degrees of inhibitory activity against strains of enterobacteria from poultry origin. The tested strains were acid resistant and were also bile tolerant. Antibiotic resistance, co-aggregation activity and hydrophobicity percentage were strain-dependent. Moreover, six strains were able to adhere to epithelial cells. Finally, six Lactobacillus strains, such as strain L. plantarum G1, L. plantarum PC2, L. viridesencs G3, L. helveticus PC6, L. delbrueckii ssp delbrueckii G7 and L. fermentum PC8, showed essential probiotic properties. The identity of the best strain L. plantarum G1 was confirmed by 16S rRNA gene sequence using PCR.